2010
DOI: 10.1177/1471301209354026
|View full text |Cite
|
Sign up to set email alerts
|

Challenges to improving end of life care of people with advanced dementia in the UK

Abstract: The end of life care received by patients with advanced dementia and their carers is of increasing importance as the incidence of dementia is set to rise in the next 30 years. Currently, inappropriate admissions to hospital are common in the UK and patients are less likely to be referred to palliative care services, receive less pain control but undergo more invasive interventions compared to their cognitively intact counterparts. Patients and families are seldom informed of the terminal nature of dementia and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
130
0

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 82 publications
(135 citation statements)
references
References 32 publications
5
130
0
Order By: Relevance
“…Academy of Medical Sciences 2016) and dementia (Thuné-Boyle et al 2010). Our findings also support predictions related to the transformative capacity of new technologies and science, tempered by complex social and institutional factors (Thimbleby, 2013;Durrani, 2016) and the projected impact of environmental factors such as climate change on the health of the population (Oven et al 2012).…”
Section: Discussionsupporting
confidence: 77%
“…Academy of Medical Sciences 2016) and dementia (Thuné-Boyle et al 2010). Our findings also support predictions related to the transformative capacity of new technologies and science, tempered by complex social and institutional factors (Thimbleby, 2013;Durrani, 2016) and the projected impact of environmental factors such as climate change on the health of the population (Oven et al 2012).…”
Section: Discussionsupporting
confidence: 77%
“…However, alongside increased community provision for end-of-life care for the frail elderly, equally crucial is the need to develop training and service provision to improve end-of-life care in hospitals and care homes -the settings where the majority of very old people die. 1,59,75,76 …”
Section: Discussionmentioning
confidence: 99%
“…40,[54][55][56][57][58] Meeting these needs in different care settings is an increasingly high priority, and lack of understanding of the course of dementia is a barrier to improving care. 59 There is growing evidence of inequitable care and poor outcomes associated with hospitalisation of older people with dementia, [60][61][62] prompting calls to improve their access to palliative care. [63][64][65][66] We found long-term-care settings provide end-of-life care for a high proportion of the oldest old with some of the highest needs in their final 'home'.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…They would also benefit from more information. A study in the UK showed that people with dementia and their carers do not understand the condition or its likely progression and, furthermore, this lack of information seems to influence decision-making, which can often lead to inappropriate care [22].…”
Section: Reviews Of the Literaturementioning
confidence: 97%